It’s been mostly about money!: a multi-method research approach to the sources of institutionalization - Casal Bértoa, Fernando (SAGE, 2015)
Although much has been written about the process of party system insti- tutionalization in different regions, the reasons why some party systems institutionalize while others do not still remain a mystery. Seeking to fill this lacuna in the literature, and using a mixed-methods research approach, this article constitutes a first attempt to answer simultaneously the following three questions: (1) What specific factors help party systems to institutio- nalize (or not)? (2) What are the links (in terms of time and degree) as well as the causal mechanisms behind such relationships? and (3) how do they affect a particular party system? In order to do so, this article focuses on the study of party system development and institutionalization in 13 postcommunist democracies between 1990 and 2010. Methodologically, the article innovates in five respects. First, it continues the debate on the importance of ‘‘mixed methods’’ when trying to answer different research questions. Second, it adds to the as yet brief literature on the combination of process tracing and qualitative comparative analysis. Third, it constitutes the first attempt to date to use a most similar different outcome/most different same outcome pro- cedure in order to reduce causal complexity before undertaking a crisp-set qualitative comparative analysis. Third, it also shows the merits of combining both congruence and process tracing in the same comparative study. Finally, it also develops a novel ‘‘bipolar comparative method’’ to explain the extent to which opposite outcomes are determined by reverse conditions and conflicting intervening causal forces.